A new alien crab for the Mediterranean Sea: Xanthias lamarckii (H. Milne Edwards, 1834) (Crustacea: Decapoda: Brachyura: Xanthidae) - CORSINI-FOKA, M.; KONDYLATOS, G.; PANCUCCI-PAPADOPOULOU, M.A. (Mediterranean Marine Science, 2013)
A single specimen of Xanthias lamarckii was collected on March 2013 from the shallow waters of Chtenia, a rocky islet near Rhodes Island, south-eastern Aegean Sea. The occurrence of this Indo-West Pacific species is reported for the first time in the Mediterranean waters and documents the ongoing process of biological invasion of the basin. The vector of introduction of X. lamarckii is unknown so far, waiting for future information on establishment and spread of the species in its new environment.